A NEW METHOD FOR ESTIMATING THE 3D SIZE-DISTRIBUTIONCURVE OF FRAGMENTED ROCKS OUT OF 2D IMAGES - Outal, Souhaïl; Jeulin, Dominique; Schleifer, Jacques (Image Analysis and Stereology, 2011)
Image analysis of rock fragmentation is used in mines and quarries to control the quality of blasting. Obtained information is the particle-size-distribution curve relating volume-proportions to the sizes of fragments. Calculation by image analysis of this particle-size-distribution is carried out in several steps, and each step has its inherent limitations. We will focus in this paper on one of themost crucial steps: reconstructing the volumes (3D). For the 3D-step, we have noticed that, due to the current acquisition method, there is no correlation between the average grey level of surfaces of the fragments and their third dimension. Consequently volumes (3D) as well as the sizes (1D) has to be calculated indirectly from the extracted projected areas of the visible fragments of images. For this purpose, we have built in laboratory a set of images of fragmented rocks resulting from blasting. Moreover, several tests based on comparisons between image analysis and screening measurements were carried out. A new stereological method, based on the comparison of the densities of probability (histograms) of the samemeasurements (with very weak covering and overlapping)was elaborated. It allows us to estimate correctly, for a given type of rock, two intrinsic laws weighing the projected areas distribution in order to predict the volumic distribution.